2016 IEEE 13th International Symposium on Biomedical Imaging (ISBI) 2016
DOI: 10.1109/isbi.2016.7493278
|View full text |Cite
|
Sign up to set email alerts
|

On comparison of manifold learning techniques for dendritic spine classification

Abstract: Dendritic spines are one of the key functional components of neurons. Their morphological changes are correlated with neuronal activity. Neuroscientists study spine shape variations to understand their relation with neuronal activity. Currently this analysis performed manually, the availability of reliable automated tools would assist neuroscientists and accelerate this research. Previously, morphological features based spine analysis has been performed and reported in the literature. In this paper, we explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…8: Average image for each cluster generated using the DNSM features. using information gain [40] and conclude that neck length is the most dominant feature for data used in this study, which confirms analysis performed in some of our previous studies [25,30].…”
Section: Morphological Features Based Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…8: Average image for each cluster generated using the DNSM features. using information gain [40] and conclude that neck length is the most dominant feature for data used in this study, which confirms analysis performed in some of our previous studies [25,30].…”
Section: Morphological Features Based Analysissupporting
confidence: 90%
“…Shi et al [7] developed a semi-supervised learning approach for spine classification based on morphological features, and used human experts for validation of their results. A recent study on spine analysis applied ISOMAP [29] to study the importance of different morphological parameters and found neck length and head diameter to be the most prominent features for mushroom and stubby spines [30]. Ghani et al [31] exploited the parametric nature of the DNSM approach and used its parameters for spine classification; they also used labels assigned by a human expert for performance evaluation.…”
Section: Related Workmentioning
confidence: 99%